2001
DOI: 10.1034/j.1600-051x.2001.028002128.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases in healthy and diseased human gingiva

Abstract: Our results did not reveal significant differences in the expression of mRNAs encoding for the MMPs between healthy and periodontitis-affected patients, reflecting the great heterogeneity in the periodontal status of individuals. However, they indicate that gingival fibroblasts are an active source of MMP-2 production in response to a periopathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 33 publications
(56 reference statements)
10
68
1
6
Order By: Relevance
“…Third, though the concentration of TIMP-1 expressed was not enough to show the difference of MMP expression between the groups, the target cells to TIMP-1 in the inflammatory areas are increased in periodontitis group compared to control group which might enhance the chance of activation 12,21) . Fourth, the activity of MMPs is tightly regulated at sev-eral levels including gene expression, secretion of pro-enzymes that require activation and inhibition by TIMPs [40][41][42][43] . Death et al 44) found that high glucose may regulate MMP gene expression via its effects on gene transcription or growth factors through the increased activation of its own response elements.…”
Section: Discussionmentioning
confidence: 99%
“…Third, though the concentration of TIMP-1 expressed was not enough to show the difference of MMP expression between the groups, the target cells to TIMP-1 in the inflammatory areas are increased in periodontitis group compared to control group which might enhance the chance of activation 12,21) . Fourth, the activity of MMPs is tightly regulated at sev-eral levels including gene expression, secretion of pro-enzymes that require activation and inhibition by TIMPs [40][41][42][43] . Death et al 44) found that high glucose may regulate MMP gene expression via its effects on gene transcription or growth factors through the increased activation of its own response elements.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that MMPs and TIMPs are involved in the physiological turnover of periodontal tissues, and MMPs appear to be involved in tissue destruction in PDs (Birkedal-Hansen, 1993, Golub et al, 2001, Reynolds et al, 1994, Van der Zee et al, 1997. However, there are contradictory results regarding the balance of MMPs/TIMPs in pathological versus healthy gingival samples (Aiba et al, 1996, Dahan et al, 2001, Garlet et al, 2004, Ingman et al, 1996, Kubota et al, 1996, Nomura et al, 1998. Some studies show a decrease in the levels of TIMPs in diseased periodontal tissues, supporting the idea that an imbalance in the levels of TIMPs/MMPs occurs in PDs and results in tissue destruction , Soell et al, 2002, Tuter et al, 2002.…”
Section: Periodontal and Pulpar Tissues Under Homeostatic Conditionsmentioning
confidence: 96%
“…And expression of MMP-2 in periodontium is localized mainly in fibroblast and granulation tissue of periodontal connective tissue(CT). In human periodontium, MMP-2 affects integrity of basement membrane and attachment of junctional epithelium and elevated MMP-2 expression level in chronic periodontitis is already reported in several investigations [15][16][17][18][19][20] . These results suggest the involvement of MMP-2 in periodontal destruction.…”
Section: ⅰ Introductionmentioning
confidence: 98%
“…MMPs, produced by both infiltrating and resident cells of the periodontium, play a role in physiologic and pathologic events. It is recognized that an imbalance between activated MMPs and their endogenous tissue inhibitors of metalloproteinases(TIMPs) leads to pathologic breakdown of the extracellular matrix during chronic periodontitis [14][15][16][17] .…”
Section: ⅰ Introductionmentioning
confidence: 99%